Isolation of a new ssDNA aptamer against staphylococcal enterotoxin B based on CNBr‐activated sepharose‐4B affinity chromatography. Issue 9 (19th April 2016) - Hedayati Ch, Mojtaba; Amani, Jafar; Sedighian, Hamid; Amin, Mohsen; Salimian, Jafar; Halabian, Raheleh; Imani Fooladi, Abbas Ali
Abstract : Staphylococcus aureus are potent human pathogens possessing arsenal of virulence factors. Staphylococcal food poisoning (SFP) and respiratory infections mediated by staphylococcal enterotoxin B (SEB) are common clinical manifestations. Many diagnostic techniques are based on serological detection and quantification of SEB in different food and clinical samples. Aptamers are known as new therapeutic and detection tools which are available in different ssDNA, dsDNA and protein structures. In this study, we used a new set of ssDNA aptamers against SEB. The methods used included preparation of a dsDNA library using standard SEB protein as the target analyte, affinity chromatography matrix in microfuge tubes, SELEX procedures to isolate specific ssDNA‐aptamer as an affinity ligand, aptamer purification using ethanol precipitation method, affinity binding assay using ELISA, aptamer cloning and specificity test. Among 12 readable sequences, three of them were selected as the most appropriate aptamer because of their affinity and specificity to SEB. This study presents a new set of ssDNA aptamer with favorable selectivity to SEB through 12 rounds of SELEX. Selected aptamers were used to detect SEB in infected serum samples. Results showed that SEB c1 aptamer (2 µg SEB/100 nM aptamer) had favorable specificity to SEB ( kd  = 2.3 × 10 −11 ). In conclusion, aptamers can be considered as useful tools for detecting and evaluating SEB. The results showed that affinity chromatography was an affordable assay with acceptable accuracy to isolate sensitive and selective novel aptamers. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Staphylococcal food poisoning, which is the result of Staphylococcal enterotoxin B (SEB), is a usual clinical complaint in patients. Many immunological methods are applied in the case of SEB detection in different nutrient and clinical samples. In this study, we set a new specific single strand DNA aptamers against SEB via SELEX procedures, aptamers purification, and affinity binding assay. Selected aptamers were performed to detect SEB in patient's serum samples. It could be considered as potent detection tools to evaluate and detect SEB.